Adjusting the Redox Coupling Effect via Li/Co Anti‐Site Defect for Stable High‐Voltage LiCoO2 Cathode. (8th December 2022) - Kong, Weijin; Zhou, Dong; Zhang, Qinghua; Wong, Deniz; An, Ke; Schulz, Christian; Zhang, Nian; Zhang, Jicheng; Liu, Xiangfeng
Abstract: High‐voltage LiCoO2 (LCO) is pressingly required for the portable electronics. But the O→Co charge transfer and the oxygen redox at high delithiation induce the issues of irreversible Co reduction, oxygen release, and unfavored phase transformation. Herein, it is proposed to tune the O→Co charge transfer via regulating Li/Co anti‐site defect with Mg 2+ and (PO4 ) 3− co‐doping to achieve a stable high‐voltage LiCoO2 cathode. The appropriately regulated Li/Co anti‐site defect enhances the redox activity of the Co‐ions, and inhibits the irreversibility of the oxygen redox and the coupled Co reduction. The increase of the formation energy of oxygen vacancies in the modified cathode at deep delithiation inhibits oxygen escape. Moreover, (PO4 ) 3− doping also stabilizes oxygen‐packed framework due to its strong bond energy with transition metal. These functions enhance the structural stability and the reversible Co/O redox ability. The improved cathode delivers a high capacity and long‐cycle capacity retention on both 4.5 and 4.6 V. This study provides some insights into adjusting the redox coupling effect and enhancing the oxygen redox reversibility by Li/Co anti‐site regulation. Abstract : Adjustment of the redox coupling effect via regulating Li/Co anti‐site defect with Mg 2+ and (PO4 ) 3− co‐doping to stabilize high‐voltage LiCoO2 cathode, is proposed. The appropriate Li/Co anti‐site defect inhibits the redox coupling of the cations, enhances the Co redox and reduces the irreversibility of oxygen redox.